Charles W. Lovett. Minute Man - Lexington, Mass. - Sampson & Murdock Co. (Tufts Archival Research Center, 2005)
Page image of Charles W. Lovett. Minute Man - Lexington, Mass. in The Boston directory for the year commencing August 1, 1925